2023
DOI: 10.1002/we.2806
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian hierarchical assessment of night shift working for offshore wind farms

Abstract: This article presents a Bayesian data‐modelling approach to assessing operational efficiency at offshore wind farms. Input data are provided by an operational database provided by a large offshore wind farm which employs an advanced data management system. We explore the combination of datasets making up the database, using them to train a Bayesian hierarchical model which predicts weekly lost production from corrective maintenance and time‐based availability. The approach is used to investigate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 49 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…The current analysis is based on the same historical database as is used by Anderson et al 12,64 It consists of supervisory control and data acquisition (SCADA), weather and operational data describing the performance, meteorological conditions and maintenance actions performed for a large group of modern, geared WTs with a multi-MW power rating. The farm utilizes a typical condition-based maintenance strategy and is located around an hour-long trip from its operational base by CTV.…”
Section: Dataset Description and Identification Of Failuresmentioning
confidence: 99%
“…The current analysis is based on the same historical database as is used by Anderson et al 12,64 It consists of supervisory control and data acquisition (SCADA), weather and operational data describing the performance, meteorological conditions and maintenance actions performed for a large group of modern, geared WTs with a multi-MW power rating. The farm utilizes a typical condition-based maintenance strategy and is located around an hour-long trip from its operational base by CTV.…”
Section: Dataset Description and Identification Of Failuresmentioning
confidence: 99%
“…This analysis is based upon the same dataset as described previously by Anderson et al [18,19]. The dataset contains operational data provided by a large offshore wind farm, consisting of a fleet of geared wind turbines with a multi-MW power rating.…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…We provide a detailed metadata table for the dataset in reference [19]. Those data-tables which are relevant for a reliability analysis are summarised in table 1, which presents the information derived and disadvantages of each data-table.…”
Section: Dataset Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method studied the effect of the shift pattern of technicians, especially the night shift corrective maintenance strategy applied in the field throughout the winter. It was found that the time-based technology availability increased by approximately 0.64% per year in specific locations [11]. Congshan L et al proposed a coordinated control strategy based on frequency division.…”
Section: Introductionmentioning
confidence: 99%